Paradigm of Financial Provision of the Agricultural Land Restoration in Ukraine - Nadiya Davydenko; Natalia Wasilewska (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
The purpose of the research was to determine the system of measures aimed at financial provision of restoration and improvement of the fertility of the agricultural lands, which are an important part of the state strategy for the development of the Ukrainian economy agrarian sector. Characteristics of land use in European countries and Ukraine were presented. The sources of financial provision of agricultural land restoration were analyzed. The measures aimed at successful restoration of fixed assets of agrarian enterprises, in particular land resources are proposed.